Utilização do controle estatístico do processo para monitoramento do peso médio de cápsulas de Tuberculostáticos: estudo de caso no NUPLAM- RN - Ferreira, Paula de Oliveira (2008)
This Master Thesis presents a case study on the use of Statistical Process Control (SPC) at the Núcleo de Pesquisas em Alimentos e Medicamentos (NUPLAM). The SPC basic tools have been applied in the process of the tuberculostáticos drugs encapsulation, primarily concerning the objective to choose, between two speeds, which one is the best one to perform the tuberculostatics encapsulation. Later on, with the company effectively operating, the SPC was applied intending to know the variability of the process and, through the tracking of the process itself, to arrive at an estimated limit for the control of future lots of tuberculostatics of equal dosage. As special causes were detected acting in the process, a cause-and-effect diagram was built in order to try to discover, in each factor that composes the productive process, the possible causes of variation of the capsules average weight. The hypotheses raised will be able to serve as a base for deepened the study to eliminate or reduce these interferences in the process. Also a study on the capacity of the process to attend the specifications was carried out, and this study has shown the process´s inaptitude to take care of them. However, on the side of NUPLAM exists a real yearning to implant the SPC and consequently to improve the existing quality already present on its medicines